KOPER-TANI (Komunitas Pertanian Terpadu Indonesia): Model Platform Digital Untuk Pembangunan Komunitas Pertanian Terpadu - Kumbara, Kumbara; Silfia, Silfia; Afrizal, Roni; Putra, Vicka Pramudya; Yelfiarita, Yelfiarita (Jurnal Pembangunan Nagari, 2025)
The limitations of integrated farming are difficult to overcome if relying solely on personal and conventional approaches. Therefore, a community-based approach with digital technology adoption is required. This study aims to analyze the initial model for developing an integrated farming community through a digital platform tailored to the characteristics and perceptions of key stakeholders. The research employs a descriptive qualitative method with data visualization techniques, using online and offline surveys involving 60 respondents—comprising farmers, consumers, and agricultural academics/practitioners—selected through quota sampling. Data analysis involved reduction, visualization of respondent characteristics in graphical form, and perception testing across respondent groups using chi-square analysis. The results were then mapped into a community program framework as the foundation for designing the initial platform model. The findings show that the Koper-Tani model aligns with user characteristics, especially regarding experience, age, and education level, which support adoption readiness. Perception tests showed no significant differences among respondent groups on the evaluated indicators. The proposed platform model consists of five subsystems: (1) needs identification and market access, (2) social media information, (3) farmer empowerment, (4) regulatory and collaboration strengthening, and (5) time-based monitoring and evaluation. Further research is needed by adding social interaction features and their impact on the sustainability of integrated agriculture.